2021
DOI: 10.1172/jci143334
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous Staphylococcus aureus induces IL-36 to enhance IgE production and ensuing allergic disease

Abstract: Boehringer Ingelheim, which is developing therapeutics targeting IL-36R inhibition in patients with atopic dermatitis and other inflammatory conditions. LSM is a full-time employee of Janssen Pharmaceuticals and holds Johnson & Johnson stock. LSM received prior grant support from AstraZeneca, Pfizer, Boehringer Ingelheim, Regeneron Pharmaceuticals, and Moderna Therapeutics, was a paid consultant for Armirall and Janssen Research and Development, was on the scientific advisory board of Integrated Biotherapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 56 publications
1
50
1
Order By: Relevance
“…In addition, a recent study showed that epicutaneous Staphylococcus aureus enhanced IgE production in an IL-36dependent manner. 40 Therefore, the skin barrier defect is likely to trigger an immune response in NS patients with no evidence for an immunodeficiency, as previously suggested. 14 Of note, the inflammatory properties of IL-17 and IL-36 pathways are enhanced by their capacity to mutually regulate each other.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, a recent study showed that epicutaneous Staphylococcus aureus enhanced IgE production in an IL-36dependent manner. 40 Therefore, the skin barrier defect is likely to trigger an immune response in NS patients with no evidence for an immunodeficiency, as previously suggested. 14 Of note, the inflammatory properties of IL-17 and IL-36 pathways are enhanced by their capacity to mutually regulate each other.…”
Section: Discussionmentioning
confidence: 71%
“…Unexpectedly, IL-4 strongly increases the expression of IL36R in macrophages. In a mouse model of atopic dermatitis, IL-4 responses were required for IL-36R signaling to elevate IgE levels ( 52 ). The anti-inflammatory profile of IL-4 combined with its role in the proliferation of tissue-resident macrophages ( 53 ) may suggest an indirect role of IL-36γ in the regulation of inflammation and in the density of AT macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous allergen immunotherapy has been suggested to be an effective therapeutic approach for AD (59,60), implying that allergen plays a pathogenic role in the development of AD. To better understand the role of cutaneous exposure to aeroallergens in AD, several mouse models of allergen-induced AD-like skin inflammation have been established and recognized as a powerful approach to analyze the allergen-induced pathophysiology of AD and elucidate the underlying mechanisms (43)(44)(45)(61)(62)(63). Of these, the OVA-induced AD mouse model has been well established (43)(44)(45); we therefore used OVA as a positive control to establish a new AD-like mouse model by using cockroach allergen.…”
Section: Discussionmentioning
confidence: 99%